(untitled) - Blumenhagen, R. (New York, 2013)
The purpose of this book is to thoroughly prepare the reader for research in string theory at an intermediate level. As such it is not a compendium of results but intended as textbook in the sense that most of the material is organized in a pedagogical and self-contained fashion
Lý thuyết dây lượng tử
Keywords: String models,Quantum field theory,Mô hình chuỗi,Lý thuyết lượng tử